Isogeometric analysis of large thin shell structures based on weak coupling of substructures with unstructured T-splines patches. (September 2019) - Liu, Zhenyu; Cheng, Jin; Yang, Minglong; Yuan, Pei; Qiu, Chan; Gao, Wei; Tan, Jianrong
Highlights: A thin shell element is developed based on unstructured analysis-suitable T-splines. The validity of the developed thin shell element is verified by a quarter sphere example. The detailed implementation of the weak coupling of substructures is introduced. A dimensionality reduction method for the sparse matrix of an IGA model is proposed. The proposed IGA with substructuring can efficiently achieve accurate results. Abstract: In this paper, a new isogeometric analysis (IGA) method is proposed for large thin shell structures based on the weak coupling of substructures with unstructured T-splines patches. Firstly, the Kirchhoff–Love shell element is developed based on unstructured T-splines for discretizing the analysis models of large thin shell structures. Subsequently, the substructuring method is adopted to divide the analysis model of a large thin shell structure into several substructures composed of multiple unstructured T-splines patches. The approach for the weak coupling of substructures is introduced in detail. To improve the IGA efficiency of large thin shell structures, a dimensionality reduction method is put forward to reduce the stiffness matrix of an IGA model by firstly condensing the interior control points of its substructures' matrices and then integrating the condensed substructures into a whole system. The effectiveness and applicability of the proposed IGA method with substructuring are verified by two examples.